(untitled) (Journal of Environmental Science and Natural Resources, 2012)
An attempt was made to investigate the seasonal (three crop seasons) trend and variability of 20 climatic variables of Dinajpur district for 1948-2004. The variety of Exploratory Data Analyses (EDA) tools and different robust and nonrobust measures are used for the analyses. The rates of total rainfall are observed positive for all the three seasons but the residuals are nonormal and/or nonstationary. The rates were found significant positive for average dry bulb temperature (+0.00655°Cyr-1) but negative for total frequency of zero rainfall (-0.0846daysyr-1) during Kharif season and significant positive for average minimum temperature(+0.0175°Cyr-1) but negative for range temperature (-0.0456°Cyr-1 ) and maximum temperature (-0.0281°Cyr-1) during Rabi season. Historical climatic data needs exploratory analysis and warrants tougher justification in classical analyses for outlier and residuals nonnormality and nonstationarity. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11549 J. Environ. Sci. & Natural Resources, 5(1): 19 28, 2012